Noble hosts: effects of internal parasites on the physiology of an intertidal brooding Sea-star - Fraysse, Cintia Pamela (2024)
Introduction: The endoparasite Dendrogaster argentinensis infects the intertidal brooder sea star Anasterias antarctica. This sea-star species is in the highest trophic level in the Beagle Channel. Objective: To study the effects of parasitism by D. argentinensis on the fitness and reproduction of A. antarctica. Methods: Adults from the brooder sea-star were collected from the rocky intertidal of Ensenada Zaratiegui bay (54°51’ S & 68°29’ W), Argentina. Eight seasonal samplings were performed (four seasons in two years) in the upper and low intertidal. During dissection, parasites were removed, and all organs were extracted and weighed separately. Results: Dendrogaster argentinensis prevalence was the highest for the region (20.4 %). Parasitized individuals were more frequent in the low intertidal in all seasons, with a higher difference in summer, where it is likely that the higher temperatures and strong winds could make the upper intertidal more challenging for a parasitized individual. Five parasitized individuals were castrated. Generally, the gonadal (GI) and somatic (pyloric caeca, PCI; stomach, SI; body wall, WI) indexes were lower in parasitized than non-parasitized individuals. Conclusions: Parasitism by D. argentinensis negatively affects A. antarctica condition. It affects reproduction because it reduces the GI, and can also produce castration. The parasite competes for the sea-stars’ energetic resources, also decreasing the individual’s capacity for feeding (reduced stomach) and growth (reduced body wall).